No association between functional catechol O-methyl transferase 1947A>G polymorphism and smoking initiation, persistent smoking or smoking cessation. - David, S; Johnstone, E; Griffiths, SE; Murphy, M; Yudkin, P; Mant, D; Walton, R (2002)
Nicotine stimulates dopamine release and activates dopaminergic reward neurones in central pathways giving rise to dependence. Catechol O-methyl transferase (COMT) inactivates extraneuronally released dopamine and is present in dopaminergic brain regions. A functional polymorphism (COMT 1947A>G) resulting in increased enzyme activity has been associated with alcoholism and polysubstance abuse. We examined the relationship between the COMT 1947A>G polymorphism and smoking initiation, smoking persistence and smoking cessation. We genotyped 266 current smokers, 270 ex-smokers and 265 lifetime non-smokers (never smokers), matched for age and gender, for the COMT 1947A>G polymorphism. Smoking status was ascertained by self-report. There was no difference in genotype frequencies between never smokers and ever smokers (current + ex-smokers); between non-smokers (never + ex-smokers) and current smokers; or between current smokers and ex-smokers. These data suggest that the COMT 1947A>G polymorphism is not associated with smoking initiation, smoking persistence or smoking cessation.